NMR Studies on the Structure of Yeast Sis1 and the Dynamics of Its Interaction with Ssa1-EEVD - Carolina O. Matos; Glaucia M. S. Pinheiro; Icaro P. Caruso; Gisele C. Amorim; Fabio C. L. Almeida; Carlos H. I. Ramos (Molecules)
HSP70 chaperones play pivotal roles in facilitating protein folding, refolding, and disaggregation through their binding and releasing activities. This intricate process is further supported by J-domain proteins (JDPs), also known as DNAJs or HSP40s, which can be categorized into classes A and B. In yeast, these classes are represented by Ydj1 and Sis1, respectively. While both classes stimulate the ATPase activity of Ssa1 (yeast HSP70) through the J-domain, only class B JDPs possess the unique ability to efficiently stimulate Ssa1 in disaggregation processes. The C-terminal EEVD motif of HSP70 plays a crucial role in mediating these interactions by connecting with both client proteins and JDPs. However, the removal of the EEVD motif disrupts the capacity of HSP70 to associate with class B JDPs, and the intricacies of the interaction between these two proteins remain incompletely understood. We employed NMR spectroscopy to investigate the structure and dynamics of the class B J domain protein (JDP) of S. cerevisiae (Sis1) complexed with an EEVD peptide of Ssa1. Our study is based on the extraordinary 70.5% residue assignment of the full-length (352 residues long) Sis1. Our findings revealed that EEVD binds to two distinct sites within the C-terminal domain I (CTDI) of Sis1, to the J domain and to the GF-rich loop located between the J domain and α-helix 6 (a structure identified by this work). We propose that the interaction between EEVD and Sis1 facilitates the dissociation of α-helix 6, promoting a conformational state that is more favorable for interaction with Ssa1. We also employed α-synuclein as a substrate to investigate the competitive nature between EEVD and the client protein. Our experimental findings provide evidence supporting the interaction of EEVD with the client protein at multiple sites and essential insights into the mechanistic cycle of class B JDPs.